A Cross sectional Study on Nurses Knowledge and Practice of Essential Newborn Care at Tertiary Care Hospitals of Bahawalpur : Nurses Knowledge and Practice of Essential Newborn Care at Hospitals - Kousar , Razia; Afzal, Muhammad; Qadir , Anam; Sakina , Robab; Asim Amin , Muhammad (Pakistan Journal of Health Sciences, 2022)
The newborn survival, growth, and development depend on the knowledge of essential infant care and correct application. The World Health Organization’s guideline is crucial, yet the majority of healthcare professionals are unaware of it and do not adhere to it. Four million infants die every year, primarily in developing countries. For every 1,000 live births in Pakistan, there are 40.4 neonatal fatalities. Objectives: To examine nurses understanding and their application of newborn care at Bahawalpur tertiary care hospitals. Methods: At Bahawalpur’s tertiary care hospitals, a cross-sectional study was done. Using a random sampling procedure, 280 registered nurses who provide labor and delivery and neonatal care were chosen. Participants were given self-administered questionnaires in order to gather data. Input and analysis of the data were done with SPSS Version 21.0. Frequency and percentages were used to present qualitative characteristics. A P value of 0.05 was employed to evaluate statistical significance. Results: Study participants averaged a 24.28 on a knowledge scale. 53.2 % of respondents had strong knowledge, while 47.8 % had low knowledge, according to the research. 52.1 % of respondents had an excellent level of practice, while 48.9 % had a low level, according to the mean practice score of 33.83. Conclusions: On some crucial aspects of neonatal care, the research population had inadequate knowledge and experience. Therefore, while assigning employees to the delivery room, preference should be given to participants with higher knowledge. Those who perform well should also be commended